2^2X(3^3+1)-5^2

asked by guest
on Jan 28, 2025 at 6:57 pm



You asked:

Evaluate the expression: 22(33+1)52{2}^{2} \left({3}^{3} + 1\right) - {5}^{2}

MathBot Answer:

22(33+1)52=87{2}^{2} \left({3}^{3} + 1\right) - {5}^{2} = 87


22(33+1)52=22(33+1)52=4(33+1)52=4(27+1)52=42852=11252=11225=87\begin{aligned}{2}^{2} \left({3}^{3} + 1\right) - {5}^{2}& = 2^{2} \cdot \left(3^{3} + 1\right) - 5^{2}\\& = 4 \cdot \left(3^{3} + 1\right) - 5^{2}\\& = 4 \cdot \left(27 + 1\right) - 5^{2}\\& = 4 \cdot 28 - 5^{2}\\& = 112 - 5^{2}\\& = 112 - 25\\& = 87\end{aligned}